2012
DOI: 10.2106/jbjs.l.01055
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in Orthopaedic Research

Abstract: Disclosure: None of the authors received payments or services, either directly or indirectly (i.e., via his or her institution), from a third party in support of any aspect of this work. One or more of the authors, or his or her institution, has had a financial relationship, in the thirty-six months prior to submission of this work, with an entity in the biomédical arena that could be perceived to influence or have the potential to influence what is written in this work. No author has had any other relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Platelets represent an accessible and inexpensive source of growth factors that have recently received considerable attention for the treatment of injured or damaged musculoskeletal tissues. 1 Enthusiasm for the therapeutic potential of platelets is based on the α-granules that contain growth factors such as transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF). 2 The growth factor concentration in platelets, coupled with the platelet concentration in blood, is sufficient to yield nanograms of growth factor per milliliter of blood without increasing the native platelet concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets represent an accessible and inexpensive source of growth factors that have recently received considerable attention for the treatment of injured or damaged musculoskeletal tissues. 1 Enthusiasm for the therapeutic potential of platelets is based on the α-granules that contain growth factors such as transforming growth factor β (TGFβ) and platelet-derived growth factor (PDGF). 2 The growth factor concentration in platelets, coupled with the platelet concentration in blood, is sufficient to yield nanograms of growth factor per milliliter of blood without increasing the native platelet concentration.…”
Section: Introductionmentioning
confidence: 99%
“…4 In some cases, PRP protocols result in a significant white blood cell content. 5 While extensive efforts are underway to understand the therapeutic benefit of PRP for tendon, ligament, and bone, 1 relatively few studies have evaluated the effect of PRP on articular cartilage and the meniscus. In a laboratory study, PRP was shown to stimulate chondrocyte extracellular matrix (ECM) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Rodeo et al. ). The importance of growth factors in combination with biomaterials lies in their influence on the main elements of tissue regeneration and the stages of bone healing (Giannoudis et al.…”
mentioning
confidence: 99%
“…The main unmet needs resulting in growth potential for the market in bone and connective tissue engineering and growth factor enhanced-bi-omaterials in orthopedics, oral and maxillofacial surgery are indications with unsatisfying therapy options to date. These include spine surgery, meniscus reconstruction, ligament replacement, revision arthroplasty, bisphosphonate-associated osteonecrosis of the jaw (alongside similar problems that may come up with novel cancer therapies), vertical bone augmentation in dental implantology, periodontology, and tumor reconstructive surgery (Warnke et al 2004;Burge et al 2007;Roccuzzo et al 2007;Chan & Leong 2008;Felice et al 2009;Yang & Temenoff 2009;Chen et al 2010aChen et al , 2010bRodeo et al 2010). The importance of growth factors in combination with biomaterials lies in their influence on the main elements of tissue regeneration and the stages of bone healing (Giannoudis et al 2008;Schindeler et al 2008;Deschaseaux et al 2009).…”
mentioning
confidence: 99%
“…For example, in a review discussing current and future direction of basic research in the field [7], 13 of the 27 references were published outside of the 25 journals included in this study. Similarly, in the three most recently published contemporary basic science reviews published in Journal of Bone and Joint Surgery , 23% [11], 39% [12], and 36% [13] of the discussed articles were published outside of these 25 journals. These findings suggest that important and potentially groundbreaking studies may come from other fields (e.g., tissue engineering or regeneration, nano-technology, cytokines and growth factors) in journals that are not commonly read by the orthopedic community.…”
Section: Discussionmentioning
confidence: 99%